Molecular Dynamics in Ag2B12H12 Studied by Nuclear Magnetic Resonance - Gradisěk, A.; Jørgensen, M.; Paskevicius, Mark; Hansen, B.R.S.; Jensen, T.R. (AMER CHEMICAL SOC, 2021)
We present a molecular dynamics study of the low-temperature polymorph of silver closo-borate α-Ag2B12H12, which is a promising ionic conductor. By means of 1H and 11B nuclear magnetic resonance spectroscopy, we identified two dynamic processes in the system that involve the movements of B12H122- cages: fast rotations with an activation energy of 308 meV and tumbling of the cages at lower temperatures with an activation energy of 67 meV. Fast rotations are known to facilitate the diffusion of Ag+ ions (the activation energy of 482 meV for ion jumps was determined from solid-state ionic conductivity measurements) while the tumbling motions are likely made possible by either impurities or local disorder, allowing for easier reorientations of the boron cages.